The Impact of Mindfulness Therapy on the Mental Health of Pregnant Women: A Literature Review - Lintje Sintje Corputty; Yosef Marsianus Karno; Abdul Thalib (Indonesian Journal of Global Health Research, 2024)
Mental health issues during pregnancy affect 15–25% of women, leading to complications such as preterm birth and low birth weight. Mindfulness-based interventions (MBIs) offer a promising non-pharmacological approach to reducing stress, anxiety, and depression while enhancing maternal and infant well-being. Objective: This review evaluates the effectiveness of mindfulness therapy in improving pregnant women's mental health by reducing anxiety, stress, and depression. A literature review was conducted using PubMed (236), ScienceDirect (106), Google Scholar (965), and Garuda (231) databases . Studies published in the last ten years (2014-2024) on the effects of Mindfulness-Based Interventions (MBIs) on maternal mental health were analyzed. From an initial 1,529 articles, only 10 studies met the inclusion criteria. MBIs, including Mindfulness-Based Cognitive Therapy (MBCT) and Mindfulness-Based Stress Reduction (MBSR), effectively reduce anxiety, stress, and depression. They improve emotional regulation, quality of life, and mother-infant bonding. Digital mindfulness interventions also show similar benefits. Mindfulness therapy significantly improves mental health during pregnancy, promoting maternal and infant well-being. Integrating MBIs into maternal healthcare services is recommended as an effective non-pharmacological approach.